Generalized optimization method for energy conversion and storage efficiency of nanoscale flexible piezoelectric energy harvesters. (15th February 2019) - Lü, Chaofeng; Zhang, Yangyang; Zhang, He; Zhang, Zhicheng; Shen, Mingzhou; Chen, Yisheng
Highlights: A scaling law is developed for designing flexible piezoelectric energy harvesters. Energy conversion efficiency depends only on two normalized system parameters. An independent law for optimizing energy storage efficiency is indispensable. Abstract: The energy conversion and storage efficiency was commonly ignored in experimental studies on nanoscale flexible piezoelectric energy harvesters (PEHs). In this study, we develop a generalized theoretical method to optimize the energy conversion and storage efficiencies of nanoscale flexible PEHs. The results are validated by comparisons with experimental measurements for various ambient excitations. A simple scaling law is established to reveal the intrinsic correlation between the efficiency of energy conversion/storage and various system parameters of the PEHs. For either the energy conversion or storage circuit, the output power density may be maximized by properly designing an intrinsic normalized parameter. Furthermore, we demonstrate that an independent optimization criterion is indispensable for standard storage circuits since including a storage module into the conversion circuit redefines the electromechanical behavior of the PEH system. The results may be used as guidelines for optimizing the energy conversion and storage efficiencies of nanoscale flexible PEHs that have promising applications in harvesting biomechanical energies.